Effect of swim suit design on passive drag - Mollendorf, J. C.; Termin, A. C.; Oppenheim, E.; Pendergast, D. R. (Medicine & Science in Sports & Exercise, 2004)
INTRODUCTION: The drag (D) of seven (7) male swimmers wearing five (5) swimsuits was investigated. METHODS: The drag was measured during passive surface tows at speeds from 0.2 up to 2.2 m x s and during starts and push-offs. The swimsuits varied in body coverage from shoulder-to-ankle (SA), shoulder-to-knee (SK), waist-to-ankle (WA) and waist-to-knee (WK) and briefs (CS). RESULTS: Differences in total drag among the suits were small, but significant. In terms of least drag at 2.2 m x s, the swimsuits ranked: SK, SA, WA, WK and CS. The drag was decomposed into its pressure drag (DP), skin friction drag (DSF) and wave drag (DW) components using nonlinear regression and classical formulations for each drag component. The transition-to-turbulence Reynolds number and decreasing frontal area with speed were taken into account. The transition-to-turbulence Reynolds number location was found to be very close to the swimmers' "leading edge," i.e. the head. Flow was neither completely laminar, nor completely turbulent; but rather, it was transitional over most of the body. The DP contributed the most to drag at low speeds (<1.0 m x s) and DW the least at all speeds. DSF contributed the most at higher speeds for SA and SK suits, whereas DP and DW were reduced compared with the other suits. CONCLUSION: The decomposition of swimmer drag into DSF, DP and DW suggests that increasing DSF on the upper-body of a swimmer reduces DP and DW by tripping the boundary layer and attaching the flow to the body from the shoulder to the knees. It is possible that body suits that cover the torso and legs may reduce drag and improve performance of swimmers.